Valor percebido, satisfação e confiança como determinantes da lealdade: um estudo no segmento de bancos de varejo - Parente, Eduardo Soares (2011)
This research has as main focus the theme loyalty in financial services, specifically in the retail banking sector. The main objectives of the study were: (1) to identify the factors that the banking customers associate as benefits, (2) to identify the sacrifices incurred by customers in retail banking, (3) to develop a customer perceived value measurement scale of banking services in Brazil, (4) to develop a theoretical model that identifies relationships between the value dimensions, satisfaction, trust and loyalty in banking segment and (5) to empirically test the nomological network of the developed model involving value, trust, satisfaction and loyalty. Initially, its was reviewed the academic literature on the topics of perceived value, trust, satisfaction, loyalty and the Brazilian banking sector, besides the relational aspects between the constructs. For the analysis of the relations it was proposed a structural model composed of thirteen (13) hypotheses. The empirical research tested the perceived value measurement scale developed for customers of banking services in accordance with the steps suggested by the literature. The empirical test was carried out in two field studies. The first consisted of 167 (one hundred and sixty-seven) undergraduate and post graduate students who use banking services and the second by 341 (three hundred forty-one) banking customers selected at different locations in the city of Fortaleza, Brazil. Its was used in the research a descriptive survey method based on primary data collection through structured questionnaires. The results were analyzed in a quantitative approach, in particular bivariate correlation analysis, multiple regression analysis and statistical techniques of structural equation modeling. Overall, the research objectives were met, with the validation of a scale to measure perceived value in banking and the confirmation of 5 (five) developed hypotheses using structural equation modeling. The confirmed hypotheses were: (1 ) Operational quality is positively related to trust, (2) Operational quality positively influences customer satisfaction, (3) Convenience access positively influences satisfaction, (4) satisfaction is directly and positively related to confidence and (5) trust directly and positively influences loyalty. At the end of the paper, indications of possible improvements for future research are discussed.